2011
DOI: 10.3109/02656736.2011.559613
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of B16 murine melanoma metastasis and enhancement of immunity by fever-range whole body hyperthermia

Abstract: The whole body hyperthermia protocol described in this work inhibits B16 tumour metastasis by inhibiting cell proliferation, neovascularisation and stimulating favourable immune responses. It demonstrated that WBH treatment benefits therapy of metastasis cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…1 Failure to treat these types of cancers by conventional therapy has enthused interest in the development of newer strategies. 2 Hyperthermia or heat therapy (typically to the tune of 41°C-47°C) is a promising strategy to combat cancers. 3 Tumor tissues are reported to be more susceptible to high temperatures as compared to normal tissues due to impaired heat dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Failure to treat these types of cancers by conventional therapy has enthused interest in the development of newer strategies. 2 Hyperthermia or heat therapy (typically to the tune of 41°C-47°C) is a promising strategy to combat cancers. 3 Tumor tissues are reported to be more susceptible to high temperatures as compared to normal tissues due to impaired heat dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Fever-level whole body hyperthermia (∼39°C-41°C) can mitigate many of these side effects and has potential to be an effective cancer treatment, but this lower heat level is thought, primarily, to stimulate the immune system and the benefits of direct thermal toxicity are reduced. 9,10 Generating localized hyperthermia at the cancer site could alleviate many of the side effects associated with whole body hyperthermia while still taking advantage of the thermal susceptibility of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, the high expression of cytokines in the spleen activates CTLs, NK cells, macrophages and monocytes, and results in increased death of tumor cells in situ. However, the expression of TNF-α mRNA in the spleen decreased slightly in the 46˚C group compared with those in the control group, while TNF-α protein was found to be either increased or unchanged in serum following early ablation (10) or mild hyperthermia (26). Further investigation is needed to explain these divergent results.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, it has been reported that hyperthermia induces a Th1-dominant immune response. The protein concentration of cytokines IL-2, IFN-γ and TNF-α was shown to increase in the peripheral blood following whole body or local hyperthermia (10,(24)(25)(26). The spleen is the largest immune organ in the body, and contains a large number of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%